Improving learning outcomes in chemical change topics through practicum activities - Dhita Fajriastiti Sativa (Jurnal Pijar Mipa, 2023)
21st-century learning requires teachers to be more creative and innovative in determining learning that activates students. The classroom action research aims to improve learning outcomes of chemical change topics through practicum activities. The research was conducted in two cycles with an achievement indicator of 85% of students having mastered concepts above the minimum completeness. The subjects studied were students of grade ten high school SMAN 5 Mataram, 35 students. Learning outcome data were collected using test and non-test instruments. The test instrument collects cognitive data, while the non-test instrument or observation sheet collects affective and psychomotor data. Achievement indicators for cognitive if 85% of students have achieved minimum completeness criteria scores (≥74), while affective and psychomotor are said to be successful if 85% of students have achieved good categories. The results showed that in cycle 1, the cognitive results had not reached the target. Only 25 (78%) students achieved minimum completion, while affective and psychomotor had reached the target. In improving learning cycle 2, the number of students who achieved minimum completion increased to 33 (94%). In conclusion, learning chemical changes through practicum activities can improve learning outcomes.